Design of an optical amplifier using an erbium-doped fiber - Tardillo, Vanessa Isabel (2009)
We present an introduction about the theoretical design of an Erbium doped fiber amplifier more known by its acronym in English as EDFA. We analyzed the gain of the amplifier as a function of the pump laser power (1480 nm and 980 nm) and size of fiber doped with Er3+.